Menelusuri nilai-nilai spiritual dalam Tradisi Megengan Jawa - Afief, Muhammad Haydar (Maliki Interdisciplinary Journal, 2023)
This study explores the spiritual values contained in the Javanese Aegean tradition. Meghan Jawa is a spiritual tradition that involves rhythmic self-cleaning ceremonies to achieve purity and balance between body, mind, and soul. Spiritual values in the Javanese Aegean tradition are closely related to harmony, alignment with the universe, and respect for the ancestors and spirits surrounding them. The research method used is qualitative by conducting a literature study that includes primary and secondary sources related to the Javanese Aegean tradition. This research identifies several spiritual values in this tradition, including awareness of a higher existence, respect for ancestors, courage to face oneself, local wisdom in dealing with life, and efforts to achieve balance and self-purity. The study results show that the Javanese Aegean tradition is important in maintaining and passing on spiritual values to the younger generation. These values serve as a guide for individuals in dealing with everyday life and help create a harmonious relationship between humans and the universe and fellow living things. Therefore, understanding and respecting the Javanese Aegean tradition can enrich spiritual life and maintain the sustainability of Javanese culture.